2017
DOI: 10.1093/medlaw/fwx004
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Emergencies of International Concern: Global, Regional, and Local Responses to Risk

Abstract: The declaration in 2009 that the H1N1 pandemic constituted a public health emergency of international concern (PHEIC) was the first such declaration under the revised International Health Regulations that were adopted in 2005. In the period since then PHEIC have been declared in relation to polio, Ebola, and Zika. This article evaluates initiatives that have been introduced globally, within the Asia-Pacific region, and within Australia, to strengthen preparedness for public health emergencies. Through analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…213 Declaration of a PHEIC under the IHR carries normative weight under international law, and allows WHO to alert and engage the international community. 214 At the same time, only 30% of states parties had reported meeting the IHR requirements to develop core health system capacities, 215 and states widely ignored WHO travel recommendations. During the Ebola epidemic, the PIP Framework was not even applicable, as its narrow scope is limited to pandemic influenza strains.…”
Section: Purpose Of Intervention Actions Necessary For Success Of Intmentioning
confidence: 99%
“…213 Declaration of a PHEIC under the IHR carries normative weight under international law, and allows WHO to alert and engage the international community. 214 At the same time, only 30% of states parties had reported meeting the IHR requirements to develop core health system capacities, 215 and states widely ignored WHO travel recommendations. During the Ebola epidemic, the PIP Framework was not even applicable, as its narrow scope is limited to pandemic influenza strains.…”
Section: Purpose Of Intervention Actions Necessary For Success Of Intmentioning
confidence: 99%
“…A key lesson from the emergence of influenza A(H1N1)pdm09 was the need for pandemic policies to be adaptable to evolving pandemic scenarios [20,21]. Many countries found that their planning assumptions did not match the expected level of pandemic impact because they were based on the more lethal HPAI H5N1 virus [22,23]. In light of the relative mildness of A (H1N1)pdm09, which still had serious consequences, countries had to rapidly adjust their plans in order to deliver a proportionate response [20].…”
Section: The Importance Of Situational Awarenessmentioning
confidence: 99%
“…It has been argued that, in spite of the 2005 revision of the International Health Regulations, preventing public health emergencies of international concern (such as Ebola and Zika) will require stronger investment in health systems, particularly in low-and middle-income countries (32). The rise of antimicrobial resistance has become a United Nations (UN) priority in recent months, emphasizing the need for a unified and global approach to reducing communicable disease threats to health (33).…”
Section: Conventional Approaches Are Necessary But Not Sufficientmentioning
confidence: 99%